COR27 and COR28 encode nighttime repressors integrating Arabidopsis circadian clock and cold response. Issue 2 (February 2017) - Wang, Peng; Cui, Xuan; Zhao, Chunsheng; Shi, Liyan; Zhang, Guowei; Sun, Fenglong; Cao, Xiaofeng; Yuan, Li; Xie, Qiguang; Xu, Xiaodong
Summary: It was noted that circadian components function in plant adaptation to diurnal temperature cycles and freezing tolerance. Our genome‐wide transcriptome analysis revealed that evening‐phased COR27 and COR28 mainly repress the transcription of clock‐associated evening genes PRR5, ELF4 and cold‐responsive genes. Chromatin immunoprecipitation indicated that CCA1 is recruited to the site containing EE elements of COR27 and COR28 promoters in a temperature‐dependent way. Further genetic analysis shows COR28 is essential for the circadian function of PRR9 and PRR7 . Together, our results support a role of COR27 and COR28 as nighttime repressors integrating circadian clock and plant cold stress responses. Abstract : COR27 and COR28 repress the transcription of evening‐phased clock genes and cold‐responsive genes, which is responsible for maintaining circadian rhythm, plant freezing tolerance and flowering time control. CCA1 directly regulates COR27 and COR28 rhythmic expression in a temperature‐dependent manner. This indicates the essential roles of COR27 and COR28 in coordinating circadian clock and cold‐stress signaling networks.